2022
DOI: 10.3389/fendo.2022.1051111
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect and safety of curcumin in women with PCOS: A systematic review and meta-analysis

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is a multi-factorial heterogeneous syndrome that has both adverse reproductive and metabolic implications for affected women and its management is a challenging clinical problem. Curcumin, as a phenolic compound with potent anti-inflammatory and antioxidant properties exerting positive effects on the lipid profile and insulin resistance, appears to be a valuable treatment regimen for patients with PCOS.ObjectiveThis study aimed to evaluate the efficacy and safety of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…A recent study has shown that the frequency of typical for PCOS menstrual abnormalities such as amenorrhea and oligomenorrhea was significantly reduced after the curcumin administration, compared to the control group [27] . Overall, curcumin was very well-tolerated and seems to be safe [25]. Moreover, the intervention reduced the hs-CRP and hirsutism score.…”
Section: Curcuminmentioning
confidence: 86%
See 2 more Smart Citations
“…A recent study has shown that the frequency of typical for PCOS menstrual abnormalities such as amenorrhea and oligomenorrhea was significantly reduced after the curcumin administration, compared to the control group [27] . Overall, curcumin was very well-tolerated and seems to be safe [25]. Moreover, the intervention reduced the hs-CRP and hirsutism score.…”
Section: Curcuminmentioning
confidence: 86%
“…Furthermore, it is claimed to have antiinflammatory, anti-cancerous, antimutagenic, cardioprotective, and radioprotective features [20] [23] [24] . For this reason, curcumin was claimed to have therapeutic potential in PCOS treatment [25].…”
Section: Curcuminmentioning
confidence: 99%
See 1 more Smart Citation
“…In women with PCOS, the level of adiponectin is lower, while this change occurs regardless of adiposity [26]. Another possible mechanism is related to the low-grade in ammation caused by PCOS and antioxidant protective effects of curcumin [30,31]. Given that obesity and unbalanced dietary composition causes more disruption in insulin metabolism and in ammation [32,33], we therefore adjusted for BMI and energy difference and other relevant factors such as age [34] and physical activity [35].…”
Section: Discussionmentioning
confidence: 99%
“…For patients who wish to have immediate fertility, oral ovulation agents should be considered [ 71 ]. PCOS treatment usually means lifelong follow-up and multiple treatments, including various treatment methods, depending on the patient’s performance, complications, wishes, and goals [ 15 , 16 , 17 , 26 , 72 , 73 ].…”
Section: Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 99%